METHODOLOGY OF TEACHING FOREIGN LANGUAGES (GERMAN) IN PRIMARY CLASSES. (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article examines the methodologies used for teaching German as a foreign language in primary classes. The focus is on age-appropriate strategies, language acquisition theories, and practical approaches that foster engagement and language retention in young learners. The role of interactive learning, the importance of cultural context, and the significance of early exposure to a foreign language are highlighted as key factors in successful language teaching.